PLATINUM GROUP ELEMENT FRACTIONATION IN A KOMATIITIC BASALT LAVA LAKE - Puchtel I.S.; Humayun M. (My University, 2001)
Precise PGE (Os, Ir, Ru, Pt, Pd) abundance data for bulk rock samples, and mineral separates, from a deep differentiated komatiitic basalt lava lake in the Vetreny Belt (Baltic Shield) were obtained using an ICP-MS ID technique. The composition of the erupted liquid (MgO = 15%) is characterized by a highly fractionated PGE pattern, (Pd/Os)N = 48, with subchondritic (Os/Ir)N = 0.43. Analysis of separated olivine and chromite revealed that Ru, Os, and Ir were slightly compatible to moderately incompatible in olivine (D = 1.7–0.8), and were compatible with chromite (D = 100–150). Platinum and Pd were highly incompatible with olivine (D = 0.08–0.03), and moderately compatible with chromite (D = 1.6–3.3). Bulk solid-liquid partition coefficients for PGEs, Ni, Cr, and Cu, estimated from the whole rock regressions, were: Os 7.9, Ir 6.6, Ru 4.5, Pt 0.53, Pd 0.09, Ni 6.2, Cr 4.4, and Cu 0.01. The highly incompatible behavior of Cu and Pd indicates that there was no separation of FeNiCu immiscible sulfide liquid during the differentiation of the lava lake. Comparison of the bulk partition coefficients with those calculated from the olivine and chromite compositions implies that the fractionating mineral assemblage included ∼10−5±1 mass fraction of pyrrhotite. The data obtained provide new constraints on the effects of fractional crystallization on the PGE compositions of mafic-ultramafic magmas.